Fat obliteration of the front sinus in recurrent frontal sinusitis: a clinical case - T. V. Banashek-Meshcheriakova; F. V. Semenov; V. G. Kolomiytsev; A. Yu. Agarkova (Кубанский научный медицинский вестник, 2020)
Aim. To describe a case of fat obliteration using platelet-rich plasma in a patient with recurrent chronic frontal sinusitis.Materials and methods. A clinical case of a 60-year-old patient who had repeatedly performed extranasal frontotomy for recurrent chronic frontal sinusitis with a short-term effect is described. Due to the ineffectiveness of conservative and traditional surgical treatment, taking into account the characteristics of the clinical picture and the presence of a cosmetic defect in the area of projection of the right frontal sinus, as well as CT results (postoperative bone defect of the right half of the frontal bone), a right-side extranasal frontotomy was performed. The operation involved sinus obliteration with adipose tissue obtained from areas of the thigh anterior surface by lipoaspiration under low pressures with the addition of platelet-rich plasma (PRP) prepared by a single centrifugation of whole venous blood. An assessment of the patient’s condition and fat transplant was carried out on the basis of objective examination after 4 and 6 months and 1.5 year after the surgery and the results of control computed tomography (CT).Results. No complaints regarding nasal breathing from the frontal sinus were registered during control examinations. A good cosmetic result and the absence of pain during palpation in the right frontal sinus were observed. According to CT results, the density of the contents of the frontal sinus corresponded to that of adipose tissue; the volume of material did not changed.Conclusion. Frontal sinus obliteration with adipose tissue and PRP addition is a promising method for treating patients with recurrent chronic frontal sinusitis and repeatedly performed extranasal frontotomy. This method has several advantages over other methods.